PENGEMBANGAN LKS IPA BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KERJA ILMIAH KELAS IV - Ariati AG, Desy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to develop a student worksheets project based learning in science teaching is done by improving the skills of scientific work of students. This research was conducted as many as six sessions using two different worksheet, the worksheet early and worksheets project based learning. The results of the initial work sheet obtained average students scientific work skills at 10.05 and the results of the Project based learning worksheets obtained average students scientific work skillsÂ at 14.88. An assessment of student worksheets project-based learning of expert learning device of 93.33, from the responses of teacher is at 100, from student responses at 89.96, the results of the worksheets based learning project categorized as feasible to use. Keywords: Student Worksheets, Project Based Learning, Scientific Work Skills